2011
DOI: 10.1002/eji.201040945
|View full text |Cite
|
Sign up to set email alerts
|

A class IA PI3K controls inflammatory cytokine production in human neutrophils

Abstract: Neutrophils are generally the first leukocytes to arrive at sites of inflammation or injury, where they release a variety of inflammatory mediators, which contribute to shaping the ensuing immune response. Here, we show that in neutrophils exposed to physiological stimuli (i.e. LPS and TNF-a), inhibition of the PI3K signaling pathway impairs the synthesis and secretion of IL-8, Mip-1a, and Mip-1b. Further investigation showed that Mip-1a and Mip-1b gene transcription was similarly decreased, whereas IL-8 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 56 publications
7
40
1
Order By: Relevance
“…In contrast, cytokine generation was not significantly affected by the p38 MAPK pathway, despite its being activated by chemoattractants and growth factors in neutrophils. Collectively, these findings diverge from the scenario observed in LPS-or TNF-stimulated neutrophils, in which the MEK/ERK, p38 MAPK, and PI3K cascades all influence cytokine production (5,8), and are all under the control of TAK1 (8,12). Finally, inhibition of the IKK/NF-kB cascade with structurally unrelated inhibitors did not affect cytokine production in fMLFand GM-CSF-stimulated neutrophils, consistent with the fact that these stimuli do not represent potent NF-kB activators in these cells (26).…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…In contrast, cytokine generation was not significantly affected by the p38 MAPK pathway, despite its being activated by chemoattractants and growth factors in neutrophils. Collectively, these findings diverge from the scenario observed in LPS-or TNF-stimulated neutrophils, in which the MEK/ERK, p38 MAPK, and PI3K cascades all influence cytokine production (5,8), and are all under the control of TAK1 (8,12). Finally, inhibition of the IKK/NF-kB cascade with structurally unrelated inhibitors did not affect cytokine production in fMLFand GM-CSF-stimulated neutrophils, consistent with the fact that these stimuli do not represent potent NF-kB activators in these cells (26).…”
Section: Discussioncontrasting
confidence: 71%
“…As an MAP3K, TAK1 acts upstream from MAPK pathways (i.e., p38 MAPK, MEK/ERK, JNK) (14)(15)(16), and can also phosphorylate IKKb (12,(17)(18)(19), thereby controlling the IKK/ NF-kB pathway. Finally, we and others have shown that TAK1 can also act upstream of other pathways, such as the PI3K/Akt axis (8,20). The activation of TAK1 implies multiple steps.…”
mentioning
confidence: 79%
See 3 more Smart Citations